Perlindungan Pekerja Migran Indonesia di Malaysia Pasca Memorandum of Understanding (MoU) Tahun 2022 dalam Kerangka Keamanan Manusia - Arsya, Shonia; Harza, Zulkifli; Jamilah, Maryam (Palito, 2024)
In April 2022, the Governments of Indonesia and Malaysia signed an MoU on “Placement and Protection of Indonesian Migrant Workers in the Domestic Sector in Malaysia” which includes recruitment and protection related to domestic workers in the domestic sector due to the large number of Indonesian Migrant Workers in Malaysia who experience acts of violence and other forms of problems working in Malaysia. This study aims to explain the form of cooperation between Indonesia and Malaysia in the placement and protection of Indonesian migrant workers in Malaysia in terms of the 2022 MoU. The research uses the concept of Human Security based on the United Trust Fund for Human Security, namely Freedom From Fear and Freedom From Want. The research method used is a qualitative explanatory type by utilizing secondary data. Based on the concepts used, the researcher found that these two components affect the survival of Indonesian migrant workers in Malaysia. The freedom from fear component, which consists of indicators in the form of personal security, shows that there are still many unfair treatment experienced by Indonesian migrant workers in Malaysia. Community security, the vulnerability of Indonesian migrant workers to victims of human trafficking. Political security, there are many cases of rights violations experienced by Indonesian migrant workers in Malaysia. Whereas in the freedom from want component, which consists of indicators in the form of Economic security, high unemployment rates, easy access to Malaysia, as well as increasing economic needs are factors of working abroad. Food security, the large number of migrant workers who experience the threat and impact of hunger, to malnutrition at work. Health security, the lack of effort and protection for the health of migrant workers in Malaysia, and Environmental security, the government's efforts to protect the safety of migrant workers working abroad.